Fusarium graminearum: pathogen or endophyte of North American grasses?. Issue 3 (21st November 2017) - Lofgren, Lotus A.; LeBlanc, Nicholas R.; Certano, Amanda K.; Nachtigall, Jonny; LaBine, Kathryn M.; Riddle, Jakob; Broz, Karen; Dong, Yanhong; Bethan, Bianca; Kafer, Christopher W.; Kistler, H. Corby
Summary: Mycotoxin‐producing Fusarium graminearum and related species cause Fusarium head blight on cultivated grasses, such as wheat and barley. However, these Fusarium species may have had a longer evolutionary history with North American grasses than with cultivated crops and may interact with the ancestral hosts in ways which are biochemically distinct. We assayed 25 species of asymptomatic native grasses for the presence of Fusarium species and confirmed infected grasses as hosts using re‐inoculation tests. We examined seed from native grasses for the presence of mycotoxin‐producing Fusarium species and evaluated the ability of these fungi to produce mycotoxins in both native grass and wheat hosts using biochemical analysis. Mycotoxin‐producing Fusarium species were shown to be prevalent in phylogenetically diverse native grasses, colonizing multiple tissue types, including seeds, leaves and inflorescence structures. Artificially inoculated grasses accumulated trichothecenes to a much lesser extent than wheat, and naturally infected grasses showed little to no accumulation. Native North American grasses are commonly inhabited by Fusarium species, but appear to accommodate these toxigenic fungi differently from cultivated crops. This finding highlights how host identity and evolutionary history may influence the outcome of plant–fungal interactions and may inform future efforts in crop improvement. Abstract : See also the Commentary on this article bySelosse et al., 217 : 968–972 .